EFEKTIVITAS PEMBELAJARAN BERBASIS DARING PADA MATA KULIAH INSYA’ DI STAI MA’ARIF SAROLANGUN: EFFECTIVENESS OF ONLINE-BASED LEARNING IN INSYA' COURSES AT STAI MA'ARIF SAROLANGUN - Mimi Permani Suci (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2020)
Abstract: Today's education world is shocked by the demands of online learning. Because the corona / covid 19 virus that emerged in Wuhan became an inevitable pandemic. The government through the general of Islamic Education has issued Circular Number 657/03/2020 concerning efforts to prevent the spread of Covid 19 (corona) within the Islamic Religious College. Ready not ready for the world of education both public and private, schools or universities are encouraged to do online learning. Following up on the government's recommendations, the lecture process at the STAI Ma'arif campus moved from being offline to online or better known as online, that also applies to the teaching and learning process of God willing subjects (writing). This research is a cualitatif research that aims to analyze the effectiveness of the teaching and learning process of God willing subjects (writing) using online-based learning. The technique used in data collection is the distribution of questionnaires to the resource persons, namely STAI Ma'arif Student, Arabic Language Education Semester IV through WhatsApp. The results of the study can be concluded that the teaching and learning process of God willing subjects (writing) by using online-based learning at STAI Ma'arif Sarolangun carried out well but not yet effective. Key words : insya’, daring, STAI Ma’arif, bahasa arab